Trilogy of Religion: The Construct of The Spiritualization of Millenial Adolescent - Rahman, Fawait Syaiful (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2022)
This paper aims to understand the spiritual revitalization of millennial youth through a religious trilogy as the three foundations of scientific foundations in Islam. This study uses a qualitative method of library research. The data analysis technique uses analysis content. The study results show that the Religion trilogy is a term from the three main foundations of Islam, namely Sharia, aqidah, and morals. Islam represents Sharia, Iman represents Akidah, and Ihsan represents Morals. Faith is, in the first place, functioning as the foundation of life. Adolescents can support various winds and storms of life if their creed or faith is of high quality; like a building, teenagers have a solid foundation that can support other buildings. The second order is Sharia; it regulates attitudes-interaction with His Lord and attitudes-interaction with others. Adolescents with good sharia quality will be able to stand up to the problems that arise in society. The third order is morality, which functions as a decoration, beautifies and beautifies the view. The Religious Trilogy must be understood correctly and adequately for success as Caliph Fi al-Ard'I has a religious-nationalist-ethical-humanistic personality.